Designing a Promotion Strategy to Increase Online Sales - Kismo, Heri; Lahindah, Laura (Jurnal Manajemen Bisnis, 2024)
This study aims to analyze the digital promotional strategies implemented by Batik Hafiyan to address the significant revenue decline caused by the COVID-19 pandemic, which led to an 80% decrease in sales in 2020. In response, Batik Hafiyan established online sales channels on platforms like Shopee, Tokopedia, Lazada, and WhatsApp. Using a qualitative research method, the study focuses on Shopee, a prominent marketplace in Indonesia with a predominantly female and fashion-oriented customer base, aligning with Batik Hafiyan's business model. Data analysis incorporates internal and external analyses, Porter’s Five Forces, SWOT matrix, and Business Model Canvas to assess value proposition and feasibility. The findings highlight the effectiveness of strategies like product discounts, Flash Sales, and targeted advertising in boosting visibility and customer engagement. The study provides practical implications for SMEs navigating e-commerce transitions, offering actionable insights into leveraging digital marketplaces for sustainable business growth amidst global challenges.